El Vaticano y el estallido de la guerra civil: el Cardenal Gomá reparó el fracaso diplomático del Marqués de Magaz - Marquina, Antonio (UNISCI Discussion Papers, 2006)
The position of the Holy See with regard to the conflict in Spain after the failed coup d’état of 17 July 1936 was very cautious, which was not understood neither by the Catholic refugees in Rome who had fled the tremendous religious persecution in the Republican zone, nor by the Nationalist diplomacy which sent the Marquis of Magaz to Rome and managed to override the ambassador of the Republic, Luis Zulueta. The unskilled diplomatic activities of the Marquis of Magaz, as well as the harsh action taken by the Nationalist government against the bishop of Vitoria and the execution by Nationalist troops of several priests who supported the Basque Nationalist Party, caused the Holy See to start considering both sides in a rather similar way. Cardinal Isidro Gomá’s trip in December 1936 managed to take the situation to a more favourable course for the Nationalist side.